Combining trace Pt with surface silylation to boost Au/uncalcined TS‐1 catalyzed propylene epoxidation with H2 and O2. Issue 1 (13th September 2021) - Wang, Gang; Du, Wei; Zhang, Zhihua; Tang, Yanqiang; Xu, Jialun; Cao, Yueqiang; Qian, Gang; Duan, Xuezhi; Yuan, Weikang; Zhou, Xinggui
Abstract: Modification of bifunctional Au‐Ti catalysts for direct epoxidation of propylene with H2 and O2 is of burgeoning interest for potential commercialization requirements with desirable overall catalytic performance. Herein, we report a strategy by combining the addition of trace Pt into Au particles to enhance hydroperoxide species formation with the surface silylation to promote propylene oxide (PO) desorption. The resultant catalyst, that is, silylated Au20 Pt1 /uncalcined TS‐1, gives rise to significantly enhanced propylene conversion of 11%, PO selectivity of 88%, and H2 efficiency of 41%. The underlying nature of the above enhanced performance is elucidated by multiple techniques, such as high‐angle annular dark‐field scanning transmission electron microscopy, X‐ray photoelectron spectroscopy, Fourier transform infrared spectra, and theoretical calculations. The insights revealed here, the synergy of Au‐Pt‐Ti triple active sites together with the surface silylation, could guide the rational design of Au‐Ti catalysts for propylene epoxidation to boost PO production.